Quantitative Analysis of Mainstream Media Coverage of the "One Belt and One Road" Initiative in Central Asian Countries - Xin, Zhang (Cultural and religious studies, 2021)
Five Central Asian countries are active participants in the construction of "One Belt and One Road". Understanding the acceptance and participation of the "One Belt and One Road" Initiative by Central Asian countries will help promote the dissemination of some relevant issues, deepen the understanding of "One Belt and One Road" Initiative among the people of the five Central Asian countries, and promote the joint development of "One Belt and One Road" to be deeper and more concrete. This paper takes the official reports related to the "One Belt and One Road" Initiative among the five countries as samples, and on the basis of sorting out the number of reports and analyzing the content of the reports, uses Python language to conduct text mining, and analyzes in detail the reporting tendency and its causes. It is found that due to the different national conditions of Central Asian countries and the development level of their cooperation with China, there are differences in the number and content of the "One Belt and One Road" Initiative reports. Therefore, in addition to strengthening political mutual trust, different communication strategies should be adopted in economic, cultural, and media cooperation to spread the "One Belt and One Road" Initiative to Central Asian countries.